2009
DOI: 10.1177/0022219409331958
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory, Short-Term Memory, and Reading Disabilities

Abstract: The purpose of the present study was to synthesize research that compares children with and without reading disabilities (RD) on measures of short-term memory (STM) and working memory (WM). Across a broad age, reading, and IQ range, 578 effect sizes (ESs) were computed, yielding a mean ES across studies of -.89 (SD = 1.03). A total of 257 ESs were in the moderate range for STM measures (M = -.61, 95% confidence range of -.65 to -.58), and 320 ESs were in the moderate range for WM measures (M = -.67, 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
266
1
18

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(313 citation statements)
references
References 139 publications
(108 reference statements)
28
266
1
18
Order By: Relevance
“…The evidence for the modality specificity hypothesis in children with MD and RD is mixed. Some studies reported modality-specific impairments in children with RD (e.g., Swanson, Zheng, & Jerman, 2009) and in children with MD (e.g., Bull & Scerif, 2001;Passolunghi et al, 2005;van der Sluis et al, 2004), whereas others reported domain-general impairments (e.g., Booth, Boyle, & Kelly, 2010;Zhang & Wu, 2011). …”
Section: Domain-generality Versus Modality-specificitymentioning
confidence: 99%
“…The evidence for the modality specificity hypothesis in children with MD and RD is mixed. Some studies reported modality-specific impairments in children with RD (e.g., Swanson, Zheng, & Jerman, 2009) and in children with MD (e.g., Bull & Scerif, 2001;Passolunghi et al, 2005;van der Sluis et al, 2004), whereas others reported domain-general impairments (e.g., Booth, Boyle, & Kelly, 2010;Zhang & Wu, 2011). …”
Section: Domain-generality Versus Modality-specificitymentioning
confidence: 99%
“…This apparent difference in phonological awareness impairments may partly be due to the increased demand on working memory in more complex phonological awareness tasks (Berninger, 2008). Children with dyslexia show deficits in their working memory, phonological awareness, and word reading efficiency (Berninger, Raskind, Richards, Abbott, & Stock, 2008; Brosnan et al, 2002; Swanson, Zheng, & Jerman, 2009). Working memory predicts both phonological awareness and word reading efficiency (de Abreu, Gathercole, & Martin, 2011; Berninger, Abbott, Vermeulen, & Fulton, 2006; Christopher et al, 2012; Locascio, Mahone, Eason, & Cutting, 2010; Ramscar & Gitcho, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In typically developing children, working memory has indeed been found to predict phonological awareness (de Abreu et al, 2011; Oakhill & Kyle, 2000) and word reading efficiency (Berninger, Abbott, Vermeulen, et al, 2006; Christopher et al, 2012; Locascio et al, 2010). Children with dyslexia generally show deficits in working memory and having phonological awareness and word reading efficiency problems (Berninger, Raskind, et al, 2008; Brosnan et al, 2002; Swanson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Due to a phonological deficit and accompanying working memory problems, children with dyslexia have problems with learning from text (e.g., Berninger, Raskind, Richards, Abbott, & Stock, 2008; Swanson, Zheng, & Jerman, 2009). Multimedia may support their learning by replacing written text with audio or by adding audio to the written text.…”
Section: Introductionmentioning
confidence: 99%